Ottoman Turks, Safavids and Mughals: The Stagnation of Islamic Civilization - Siti Rodhiyah; Zaini Dahlan (Saniya Institute, 2023)
The purpose of this research is to see how the history of Islamic civilization during the Ottoman Turks, Safavids and Mughals in the 17th-18th centuries. In this research, the researcher uses a literature study by collecting research data from the treasures of literature and making the world of texts the main material for analysis. The results of this study show that Islamic civilization during the Ottoman Turks, Safavids and Mughals in the 17th-18th centuries experienced a significant rapid stagnation starting from the economic, cultural, ruler morality and military fields. This was due to the weak regulatory framework, financial decline, and the emergence of rebellious figures both from within the country and from abroad. So, it is no wonder then that Islam can no longer be the center of attention of world civilization.